P2.032 A National Quality Assurance Survey: Low Neisseria Gonorrhoeae Misidentification Rates in Australia, 2012. (13th July 2013) - Trembizki, E; Lahra, M M; Stevens, S; Freeman, K; Hogg, G; Lawrence, A; Pearson, J; Smith, H; Sloots, T; Whiley, D
Abstract : Introduction: Commercial biochemical tests are typically used for the identification of N. gonorrhoeae isolates, however certain methods can exhibit specificity problems when testing commensal Neisseria strains. The aim of this study was to assess rates of phenotypic misidentification of N. gonorrhoeae in Australia. Methods: A total of 2373 isolates were received from reference laboratories throughout Australia in the first half of 2012, and comprised 98% of all gonococci isolated in Australia during this period. To confirm organism identity, all isolates were tested using in-house N. gonorrhoeae real-time PCR assays targeting multicopy opa, porA pseudogene and cppB genes. Results: The results showed that 98.5% (2336/2373) of isolates were positive for all three gene targets, 31 positive for two targets (3 porA -negative, 1 opa negative and 27 cppB -negative) and 6 were negative by all 3 PCR targets. Using 16S rDNA sequencing, 4 of the latter 6 isolates were determined to be non-gonococcal species ( Moraxella and commensal Neisseria ) whereas two isolates could not be identified. Using PCR as the reference standard, the results showed that phenotypic identification of N. gonorrhoeae in Australia is highly accurate at 99.8%. Conclusions: To date, this national quality assurance survey represents the most comprehensive assessment of phenotypic-based misidentification rates of N.gonorrhoeae isolates in Australia and elsewhere. Moreover, we demonstrated that Australian reference laboratories have maintained very low rates of phenotypic based misidentification (∼0.2%). Further, the results highlight the need to use 2 distinct sequence targets for PCR-based detection of N. gonorrhoeae so as to avoid false-negative results.